Prevalence of Escherichia coli Resistance Genes in Mullet Fish - Elsharawy, Nagwa T.; Ramadan, Mariem A.A.; Elsayed, Abeera M. (Journal of Advanced Veterinary Research, 2023)
Escherichia coli gene mutations (plasmids, integrons, and transposons) have instigated multidrug resistance (MDR) against various antimicrobials. This study detected antibiotic-resistance genes (genotypic and phenotypic) in E. coli and performed Whole-genome sequencing to discover MDR-associated E. coli genes in mullet fish. E. coli isolates were serologically identified and their antimicrobial sensitivity was tested. E. coli presence was confirmed in 35% of the mullet fish samples. Cephalosporins, tetracyclines, and sulfonamides presented higher efficiency against E. coli. The serological investigation revealed the presence of STEC (O157:H7, 50%), ETEC (O142, 20%), EHEC (O26:H11,15%), and EPEC (15%) in mullet meat samples. A symmetrical band represented the Subunit B of the Shiga-like toxin (SLT) genewhereas the Heat-labile toxin (LT) gene was found in plasmid and genomic DNA-detected strains. The results revealed the hazardous nature of STEC for mullet meat consumers. The study recommends improving the hygienic conditions during the mullet handling and processing steps, which will minimize antibiotic usage and resistance.